2019
DOI: 10.1136/bmjopen-2018-024737
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of surgical fixation for lateral compression type one (LC-1) fragility fractures of the pelvis: a systematic review

Abstract: ObjectivesTo undertake a systematic review of the evidence base for the effectiveness of surgical fixation of lateral compression (LC-1) fragility fractures of the pelvis compared with non-surgical approaches.SearchesMEDLINE, EMBASE, the Cochrane Central Register of Controlled Trials and two international trials registers were searched up to January 2017 (MEDLINE to February 2019) for studies of internal or external fixation of fragility fractures of the pelvis.ParticipantsPatients with lateral compression pel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…We noted a previous systematic review of four studies on the effectiveness of surgical fixation of osteoporotic LC1 fractures. This found insufficient evidence to support guidance on the most effective treatment for patients sustaining this injury however where reported, mobility and function did improve after surgery [ 59 ]. This systematic review is a more comprehensive overview of 17 studies encompassing all types of FFP.…”
Section: Discussionmentioning
confidence: 99%
“…We noted a previous systematic review of four studies on the effectiveness of surgical fixation of osteoporotic LC1 fractures. This found insufficient evidence to support guidance on the most effective treatment for patients sustaining this injury however where reported, mobility and function did improve after surgery [ 59 ]. This systematic review is a more comprehensive overview of 17 studies encompassing all types of FFP.…”
Section: Discussionmentioning
confidence: 99%
“…We noted a previous systematic review of four studies on the effectiveness of surgical xation of osteoporotic LC1 fractures. This found insu cient evidence to support guidance on the most effective treatment for patients sustaining this injury however where reported, mobility and function did improve after surgery [59]. This systematic review is a more comprehensive overview of 17 studies encompassing all types of FFP.…”
Section: Discussionmentioning
confidence: 95%
“…A systematic review found no robust evaluations, particularly randomised controlled trials (RCTs), of the effectiveness of internal fixation with INFIX in patients with osteoporotic LC-1 fractures [ 23 ]. The review identified five case series, with four being retrospective.…”
Section: Introductionmentioning
confidence: 99%